Geomorphology of the canton of Siquirres, Costa Rica - Arroyo-González, Luis Nelson (2021)
This article is part of an environmental diagnosis that represents a section of a survey intended to be used for the creation of the Regulatory Plan (i.e., land use regulations) for the canton of Siquirres. With the intention of characterizing geological and geomorphological aspects, use was made of technical reports, thematic maps, aerial photographs and field work activities. Demarcation and classification of landforms was carried out and, thereafter, each landform was assigned potential natural hazards. The survey constitutes an input for realizing the tasks involved in cantonal territorial planning through the use of the Regulatory Plan instrument.